Malignant Fibrous Histiocytoma of the Kidney Treated with Nephrectomy and Adjuvant Radiotherapy: A Case Report - Rita Marchese; Pantaleo Bufo; Giuseppe Carrieri; Giuseppe Bove (Case Reports in Medicine)
Malignant fibrous histiocytoma (MFH) usually presents in the extremities or retroperitoneum. Cases involving the kidney are rare and portend a poor prognosis. Although radical nephrectomy is the most beneficial curative choice for this neoplasm, patients are often treated with adjuvant chemotherapy due to high risk of local recurrence and distant metastases. We describe a case of a 68-year-old woman affected by MFH, treated with both nephrectomy and radiotherapy without systemic therapy showing an unexpected twenty-four-month postsurgery survival outcome.